Individual differences in the preference for cross-sex friendship (heterosociality) in relation to personality. (15th April 2020) - Altmann, Tobias; Roth, Marcus
Abstract: A common focus of previous research on friendship has been on similarity and homophily (attraction of similarity) based on individual characteristics. With respect to homophily based on gender, previous research has provided considerably stronger evidence for homosociality than for heterosociality, meaning that people on average prefer same-sex over cross-sex friendships. However, these studies have also shown substantial individual differences in these preferences (e.g., some women and men prefer cross-sex over same-sex friendships). Only a few studies have attempted to explain these differences, most of them focusing on only special types of friends (e.g., three best friends) and assessing only isolated personality traits. Our goal here was to contribute to the understanding of heterosociality by selecting the best predictors from a larger set of personality variables with a research design that allowed us to differentiate between cross-sex and same-sex friends among close and general friends in women and men ( N  = 331). Results showed that openness and conscientiousness of the Big Five, gender role identification, homophobia, and cultural rigor but not self-esteem significantly explained variance in heterosociality, although variance explained was small. Implications for understanding gender differences and gender preferences in friendship formation are discussed.